KONDISI UMKM MASA PANDEMI COVID-19 PADA PERTUMBUHAN EKONOMI KRISIS SERTA PROGRAM PEMULIHAN EKONOMI NASIONAL - Arin Ramadhiani Soleha (Universitas Teuku Umar, 2020)
This research examines the condition of Micro, Small and Medium Enterprises (MSMEs) on Indonesia's economic growth during the Covid-19 pandemic that we experienced from March to September 2020. This research also examines the government's efforts to encourage MSMEs to keep running in times of economic crisis. this. The purpose of this study is to determine the extent to which MSMEs survive the continuity of economic growth in Indonesia. This type of research is a qualitative descriptive analysis. This data collection method is obtained from secondary data. From the results of data analysis, it can be concluded that MSMEs are able to encourage economic growth in Indonesia, of course, assisted by government policy efforts.Keywords: Economic Growth, Economic Recession, Government Policy Efforts, MSME, Pandemic.